Integration of Cultural Content Between Arabic and Indonesian in Arabic Textbooks for Non-Native Speakers - Rosyad, Muh Sabilar; Qomaruddin, Farid (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This research aims to explain the integration steps in selecting cultural content in the target language and mother tongue (Indonesian) and its design in Arabic language learning books for foreign speakers. This research uses a descriptive method that combines with a qualitative approach. The data sources are Arabic language lecturers and textbooks, as well as several students from Arabic language education study programs. Researchers act as the main instrument in collecting data through in-depth interviews, observation, and documentation. All data received is checked through source triangulation and analyzed through interactive descriptive techniques. The result of this research is cultural content that has similar behavior in both languages is arranged in the form of themes and topics for teaching materials, and the integration process is based on student suggestions considering the cultural aspects that are most appropriate and relevant in both Arab countries and Indonesia. A textbook that integrates the cultures of both languages are very interesting and able to provide various conveniences in learning Arabic for non-native speakers.